2006
DOI: 10.1016/j.asieco.2006.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cost study of foreign and Thai domestic banks in 1990–2002: Its policy implications for a desirable banking industry structure

Abstract: This paper investigates the changing cost performances of foreign and domestic banks in Thailand in relation to increased foreign bank penetration by estimating their cost functions using panel data from 27 banks during 1990-2002. Our empirical analysis suggests that production technologies of foreign bank branches are distinct from those of Thai domestic banks. After the Asian crisis, financial reforms increased operating costs of domestic banks and reduced costs of foreign bank branches. Foreign acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 21 publications
0
21
0
2
Order By: Relevance
“…This result could be explained by foreign investment theory, which states that foreign ownership has a significant effect on firm value by improving its performance. Theoretically, it is found that higher proportion of foreign ownership has positive association with company's performance because it introduces advanced information technology and leads to greater economic efficiency (Claessens et al, 2001;Okuda & Rungsomboon, 2004;Anandarajan & Hasan, 2010).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…This result could be explained by foreign investment theory, which states that foreign ownership has a significant effect on firm value by improving its performance. Theoretically, it is found that higher proportion of foreign ownership has positive association with company's performance because it introduces advanced information technology and leads to greater economic efficiency (Claessens et al, 2001;Okuda & Rungsomboon, 2004;Anandarajan & Hasan, 2010).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…El estudio efectuado por Hidenobu Okuda y S. Rungsomboon (Okuda, 2006) sobre la presencia de la banca extranjera en Tailandia, investiga el cambio en la tecnología de producción de los bancos extranjeros y domésticos sugiriendo que los bancos extranjeros y domésticos tiene diferencias en sus ventajas de información y procesamiento. Después de la crisis de Asia, la aplicación de medidas más estrictas en la regulación mejora el rendimiento de los costos comparativos de los bancos extranjeros.…”
Section: Revisión De La Literaturaunclassified
“…Por ejemplo, Hidenobu Okuda (2006) investiga los cambios en las tecnologías de producción de los bancos extranjeros y domésticos de Tailandia, en relación al aumento de la penetración de la banca extranjera mediante la estimación de las funciones de costos de 28 bancos.…”
Section: Revisión De La Literatura Sobre El Temaunclassified